Propuesta arquitectónica para un parque tecnológico en Popayán - Ruiz Morales, Bryan Javier (Universidad Antonio Nariño, 2021)
Through an exhaustive analysis, it is possible to determine that Colombia doesn’t have a fully established space dedicated to the progress and development of new technologies, which generates a delay in sectors like the creation and innovation, which allow to boost the country's economy and improve the quality of life of its inhabitants. Through an investigative process, we seek to find the main factors by which this deficiency occurs, tackling the country at both a macro, meso and micro level; managing to establish its weaknesses, strengths and threats, until it is possible to determine a suitable place, in which a solution to the main problem can be implemented, which is intended to be developed through the implementation of equipment that meets the necessary requirements to promote said sector.